A Descriptive Content Analysis of Web of Science Studies on Teacher Image (2015–2024) - Karagöl, İbrahim (Global Educational Research Review, 2025)
Purpose –  The aim of this research is to conduct a descriptive content analysis of studies on teacher image and to determine the trends in these studies. Methods/Design/Approach – This research uses document analysis, employing descriptive content analysis to examine studies related to teacher image. This analysis included frequency-based coding to quantify the occurrence of specific keywords and themes related to teacher image. The Web of Science database was searched using the keywords teacher image, professional image, and occupational image. After reviewing titles and abstracts of the retrieved studies, 10 studies relevant to the research scope were selected for final analysis. Findings – This descriptive content analysis of 10 studies reveals a diverse range of approaches to studying teacher image, reflecting the complexity of the construct. Qualitative methods are predominant in the studies analyzed. The study highlights the influence of media, policy, cultural values, and other factors on perceptions of teacher image. Originality/Value – This study offers a focused descriptive content analysis of teacher image research. It highlights the prevalence of qualitative methods and the need for quantitative/longitudinal studies, guiding future research. Practical Implications – The study proposes strategies to combat negative stereotypes and enhance teacher image by addressing sociological, cultural, and media influences. Keywords Teacher image, professional image, media representation, educational perception, document analysis Paper type Research paper